PENGARUH EKSTRAK METANOL DAUN PALIASA (Kleinhovia hospita, Linn) TERHADAP LAMBUNG MENCIT - Mustapa, Mohammad Adam (Jurnal Entropi, 2006)
The research about the effect of extract methanol ? Paliasa? leaves (Kleinhovia hospita, Linn) to gastric of mice have been done, which is given orally to improve the scientific data in development of ? Paliasa? Plant as tradisional drug for some kinds of desease. This research has used lest animals of fifteen male micethat divided into 5 groups. Groups I,II,III have been given suspension of extract methanol with 5 % w/v, 10 % w/v and 15 % w/v during 7 days. Group IV has been given acetosal suspension 0,195 % as comparement. Group V have been given Na-CMC as control. Observasion have been done in daya of 8 th then operated the astric of mece which is separated and observea mether there is a gastric ulcer such as blood spot perforation. The result showed that there is no effect to the gastrik of mice by the methanol extract of paliasa leaves.